How Can Cattle Be Toilet Trained? Incorporating Reflexive Behaviours into a Behavioural Chain - Neele Dirksen; Jan Langbein; Lars Schrader; Birger Puppe; Douglas Elliffe; Katrin Siebert; Volker Röttgen; Lindsay Matthews (Animals, 2020)
Untrained cattle do not defecate or urinate in defined locations. The toilet training of cattle would allow urine and faeces to be separated and stored, reducing climate-damaging emissions and improving animal health. In a proof-of-concept study, we evaluated a novel protocol for toilet training in cattle. Five heifer calves (and yoked controls) were trained in the voluntary (operant) behaviours of a toileting chain. Then, reflexive urinating responses were incorporated into the chain, with toileting signalled by a tactile (vibratory) stimulus. On 95% of occasions, the calves inhibited/interrupted urination when receiving the stimulus, and on 65% of these occasions, reinitiated urination in the latrine. Furthermore, during 63% of urinations in the latrine, the calves oriented to the reward location before any food was delivered, providing additional evidence that calves can be successfully toilet trained with food rewards. Yoked controls failed to learn most of the operant elements and all the reflexive responses of toilet training. The results show that reflexive behaviours can be incorporated into voluntary toileting sequences with cattle and extend the range of species that can be toilet trained. Future refinement of the protocol to allow training under practical farm conditions offers the potential to mitigate climate damage and improve animal health.